Dependence of the service speed on the provision of transit trains with locomotives on the Koshta — Babayevo railway section - M. I. Mekhedov; N. V. Kornienko; A. S. Adadurov (Вестник Научно-исследовательского института железнодорожного транспорта, 2023)
Introduction. Today, ensuring stable train traffic remains relevant, particularly on the heavy traffic lines of the Russian Railways network. Solutions to this problem largely involve the development of polygon technologies based on harmonised use of the infrastructure, locomotive and car fleets. This requires the elimination of bottlenecks, which in the future would help increase service speed on long railway lines.Materials and methods. Since service speed is an important quality indicator that identifies rail sections and lines with traffic obstruction, the authors applied the service speed method, in order to identify bottleneck sections and their causes.Results. The authors consider the operating results of the double-track heavy traffic line of Koshta — Volkhovstroy-I of the Oktyabrskaya Railway, which joins sections with DC (Volkhovstroy-I — Babayevo) and AC (Koshta — Babayevo) electric traction. At the docking station, the authors assessed the impact of providing freight trains with locomotives on the service speed of loaded train traffic to the ports of the North-West, identified the bottleneck and analysed the transportation performance on the line under consideration. The authors propose a new method for reserving the locomotive fleet at docking stations of DC and AC railway sections, which enables to determine the necessary technological reserve of locomotives depending on the established service speed standard, given all operational changes in the organisation of transportation with full shortage compensation of locomotives.Discussion and conclusion. The authors found that the bottleneck interferes with the steady traffic of loaded trains. In the area under study, this is due to infrastructural limitations of traction power supply. The authors consider options for strengthening the traction power supply system by harmonising AC and DC locomotive fleets. The proposed steps to eliminate the bottleneck would help achieve significant technological effects in the railway line operation.